2008
DOI: 10.5432/ijshs.ijshs20080323
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Analysis of the Snatch Technique used by Japanese and International Female Weightlifters at the 2006 Junior World Championship

Abstract: The purpose of the present study was to compare the snatch techniques of Japanese and international female weightlifters using kinematic analysis. Motion analysis of the snatch techniques conducted using videos recorded at the 2006 Women's Junior World Weightlifting Championship. The results indicated no significant differences between the snatch techniques of Japanese and international weightlifters in terms of the kinematic parameters expressed by the barbell trajectory and joint angles. However, the interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
(28 reference statements)
1
3
0
3
Order By: Relevance
“…In other words, an unsuccessful lift occurs not only when the lifted weight exceeds the lifters’ weight maximum, but when technical factors are at play. Studies on snatch performance have focused mainly on the differences between superior and inferior lifters, or the difference between the lifted barbell weight with respect to barbell kinematics, kinetics, and joint kinematics [1,2,3]. Measurement findings of these studies revealed that the skill of the second pull phase, including lower limb joint kinematics and barbell kinematics, is important for a successful heavy snatch lift.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, an unsuccessful lift occurs not only when the lifted weight exceeds the lifters’ weight maximum, but when technical factors are at play. Studies on snatch performance have focused mainly on the differences between superior and inferior lifters, or the difference between the lifted barbell weight with respect to barbell kinematics, kinetics, and joint kinematics [1,2,3]. Measurement findings of these studies revealed that the skill of the second pull phase, including lower limb joint kinematics and barbell kinematics, is important for a successful heavy snatch lift.…”
Section: Introductionmentioning
confidence: 99%
“…El tiempo se midió desde el último momento en que la barra se encontraba en el suelo. El uso de videograbaciones es usual para definir las características biomecánicas externas del levantador de pesas y de la barra; ejemplos de esto son los trabajos de Isaka et al (1996); Shilling et al (2002); Okada et al (2008) y Musser (2010).…”
Section: Procedimiento Para Obtener La Trayectoria Y Magnitudes Vertiunclassified
“…Other authors (Korkman & Harbili, 2015;Hoover et al, 2006;Campos et al, 2006) have determined that absolute and relative indices of the barbell departure amplitude and squat depth decrease with weight gain. According to Japanese experts (Ikeda et al, 2012;Okada, et al, 2008) the difference between maximum amplitude of barbell departure and the amount of displacement in supporting squat phase should be minimal. At the same time Ho час et al, (2014) Gourgoulis et al, (2010) believe that the amplitude of barbell movement into supporting squat is influenced not as much as by the level of athlete's physical fitness, but as by their individual characteristics.…”
Section: Introductionmentioning
confidence: 99%